2020
DOI: 10.1136/bmjopen-2019-036483
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wide field imaging by nurses with indirect ophthalmoscopy by ophthalmologists for retinopathy of prematurity: a diagnostic accuracy study

Abstract: ObjectivesRetinopathy of prematurity (ROP) is a vasoproliferative disease of the preterm retina with the potential to cause irreversible blindness. Timely screening and treatment of ROP are critical. Neonatal nurses trained in wide field digital retinal photography (WFDRP) for screening may provide a safe and effective strategy to reduce the burden of ophthalmologists in performing binocular indirect ophthalmoscopy (BIO). The objective of the study was to determine the diagnostic accuracy of WFDRP in the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…An alternate approach to ROP screening involves the use of wide-field digital retinal imaging (WFDRI). This mode of non-contact imaging can be performed by trained personnel other than an ophthalmologist, 3 which would drastically contribute to efficiency of image capture and increase the volume of screened infants at a time. A prospective cohort study by Prakalpakorn et al 15 showed that non-contact cameras are well tolerated and less stressful to the infant.…”
Section: Bio Versus Wfdrimentioning
confidence: 99%
“…An alternate approach to ROP screening involves the use of wide-field digital retinal imaging (WFDRI). This mode of non-contact imaging can be performed by trained personnel other than an ophthalmologist, 3 which would drastically contribute to efficiency of image capture and increase the volume of screened infants at a time. A prospective cohort study by Prakalpakorn et al 15 showed that non-contact cameras are well tolerated and less stressful to the infant.…”
Section: Bio Versus Wfdrimentioning
confidence: 99%
“…Indeed, it overcomes several limitations of other imaging methods, such as sedation and intravenous dye injection [ 25 ]. Moreover, as previously demonstrated by Athikarisamy et al, performing quality wide-field imaging may also help in an off-site telehealth diagnosis of all patients with referral-warranting pediatric retinal diseases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“… 7 16 It also has good accuracy (sensitivity over 70%) in identifying clinically significant (type 2 or worse) ROP when compared with indirect ophthalmoscopy. 17 18 …”
Section: Introductionmentioning
confidence: 99%
“…Portable WFDI as an ROP screening method was proven, despite the high initial cost of the equipment, to be a cost-effective strategy 7 16. It also has good accuracy (sensitivity over 70%) in identifying clinically significant (type 2 or worse) ROP when compared with indirect ophthalmoscopy 17 18…”
Section: Introductionmentioning
confidence: 99%